2017
DOI: 10.1021/acs.jafc.7b00434
|View full text |Cite
|
Sign up to set email alerts
|

Associations among Protein Biomarkers and pH and Color Traits in Longissimus thoracis and Rectus abdominis Muscles in Protected Designation of Origin Maine-Anjou Cull Cows

Abstract: This study investigated the relationships among a list of 23 protein biomarkers with CIE-L*a*b* meat color traits and ultimate pH on Longissimus thoracis (LT) and Rectus abdominis (RA) muscles of 48 protected designation of origin Maine-Anjou cows. The technological parameters were correlated with several biomarkers and were in some cases muscle-dependent. More biomarkers were related to pHu in LT than in RA muscle. Some consistencies were found, by the common correlation of pHu with MyHC-IIa and MyHC-IIx. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(96 citation statements)
references
References 49 publications
9
67
1
Order By: Relevance
“…However, a number of studies demonstrated opposing results . Previous studies have indicated that gene expression levels might depend on breed, nutrient conditions, or epigenetic mechanisms . Hence, it is thought that the contrary differences with our results may occur due to these reasons.…”
Section: Resultscontrasting
confidence: 93%
See 2 more Smart Citations
“…However, a number of studies demonstrated opposing results . Previous studies have indicated that gene expression levels might depend on breed, nutrient conditions, or epigenetic mechanisms . Hence, it is thought that the contrary differences with our results may occur due to these reasons.…”
Section: Resultscontrasting
confidence: 93%
“…A number of studies have asserted that CAST , HSPB1 , and HSPA1A genes and their proteins affect meat quality. However, some studies proposed that the CAST gene was not associated with meat quality .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationships were investigated (i) irrespective of the M and of other factors of variation and (ii) for each M, irrespective of the other factors of variation. For regression analysis, the ‘optimal model’ explaining maximal variability option was used . The percentage of variability in meat tenderness explained by the explanatory variables was based on the r 2 value of the regression analysis × 100.…”
Section: Methodsmentioning
confidence: 99%
“…JFDS-2019-0740 Submitted 5/15/2019, Accepted 9/2/2019. Authors are with Jilin Agricultural Univ., 2888 In addition to the color stability, meat metabolite profiles, flavor, volatiles, pH value, moisture content as well as water holding capacity (WHC) are susceptible to environment changes (Fadahunsi, Dejoh, & Onilude, 2015;Gagaoua, Couvreur, Le, Aminot, & Picard, 2017;Jia et al, 2018;Reis, Reis, Mills, Ross, & Brightwell, 2016). WHC, the water retaining ability of meat, is a major quality index.…”
Section: Introductionmentioning
confidence: 99%